The relationship between need for closure and compliance to harsh power tactics in high demanding jobs: A study conducted among firefighters and social workers. Issue 10 (27th July 2020) - Di Santo, Daniela; Tesi, Alessio; Aiello, Antonio; Pierro, Antonio
Abstract: The present research aimed at expanding Pierro, Kruglanski, and Raven's work examining the interweaving between the need for closure (NFC; the desire to form quick and unambiguous knowledge) and the Interpersonal Power Interaction model. In particular, this study explored the idea that the greater compliance to harsh power tactics of subordinates' employees, that are high on NFC, can increase when their desire to achieve cognitive closure is made more salient by a high (compared to low) level of perceived job demands. A sample of 280 subordinates employees belonging to two different organizational contexts filled in a self‐report questionnaire. Through a moderation and simple slope analyses, we tested and confirmed our hypothesis. When job demands were high, it potentially impaired the subordinates' chance to form a quick knowledge. As a result, high NFC subordinates showed a higher compliance with harsh power tactics. Such tactics, limiting the subordinates' freedom of choice, can be conceived as a means to gain quick knowledge when the organizational context is perceived as particularly demanding. As far as practical implications, these results suggest that for high NFC subordinates the use of more directive and unambiguous guidelines (e.g., harsh power tactics) could minimize the scarcely tolerated cognitive cost associated with high job demands.